Vocational pedagogies and benefits for learners : practices and challenges in Europe - (:unkn) unknown (Publications Office of the European Union, 2015)
"This Cedefop research paper examines the role played by learning outcomes approaches in pedagogical change in initial vocational education and training (VET) in 15 EU Member States. Understanding the effects of vocational pedagogies, and particularly of learner-centred approaches, matters. It enables policy-makers to develop models and tools which can help VET teachers and trainers more effectively match teaching and learning methods to the needs of their students and their contexts. Through such means, vocational pedagogies can directly impact on the quality of teaching and learning, and achieving VET's wider goals. The study builds upon previous evidence published by Cedefop on the design and delivery of learning outcome-based curricula which have drawn attention to the importance of appropriate pedagogies for achieving intended learning outcomes. It examines the benefits that learner-centred pedagogies have for learners and discusses the way that teachers and trainers, learning environments and learning materials support or hinder pedagogical change." (Editor, BIBB-Doku)